Clinical-epidemiological aspects of patients submitted to Percutaneous Coronary Intervention in a university hospital - Maria Solange Moreira de Lima; Rodrigo Assis Neves Dantas; Neyse Patrícia do Nascimento Mendes; Louise Constância de Melo Alves; Tamara Taynah Medeiros da Silva; Andréa Gomes da Rocha Brito; Daniele Vieira Dantas
ABSTRACT Objective: To outline the clinical-epidemiological profile of patients submitted to Percutaneous Coronary Intervention in a Reference Hospital in Urgent Cardiology Clinic of the state of Rio Grande do Norte. Method: This is a descriptive, exploratory, prospective study with a quantitative approach developed in a Brazilian University Hospital with patients submitted to Percutaneous Coronary Intervention. Data collection occurred between April and October 2017. Results: The sample consisted of 222 patients, of whom 58.10% underwent Elective Percutaneous Coronary Intervention and 41.89% were primary, 65.3% males, with a mean age of 62.7. In comorbidities "Hypertension", "Acute Myocardial Infarction", "Current Smoking" and "Physical Inactivity" were highlighted. Conclusion: In the elective patients, there was a high prevalence of risk factors and in patients with urgent cases, high time of total ischemia. It is necessary to create strategies to structure the care line, to improve the effectiveness of treatment and to minimize adverse outcomes.